Principles of so-called „material” and „formal” truth. A logical, philosophical and juridical analysis - Łukowski, Łukasz; Żukowski, Bartosz (Acta Universitatis Lodziensis. Folia Iuridica, 2014)
Concepts of material and formal truth have a long and well-grounded tradition in the doctrine of law. It seems, however, that they need some clarification and conceptualisation in purely philosophical and logical terms. In this paper, we propose such a theoretical analysis. These considerations are followed by a review of the key aspects of the current Polish legislation, which is written from the point of view of the conclusions reached through the first level of analysis.